2022
DOI: 10.1177/21925682221095470
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Respiratory Dysfunction for Cervical Spinal Cord Injury and/or Cervical Fractures in Elderly Patients: A Multicenter Survey

Abstract: Study design Retrospective Cohort Study Objective The purpose of this study was to investigate the prognosis of respiratory function in elderly patients with cervical spinal cord injury (SCI) and to identify predictive factors. Methods We included 1353 cases of elderly cervical SCI patients collected from 78 institutions in Japan. Patients who required early tracheostomy and ventilator management and those who developed respiratory complications were defined as the respiratory disability group. Patients’ backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The accurate prediction of prognosis for a certain disease or trauma has been one of the main goals of rehabilitation medicine. For this reason, many studies have been conducted to evaluate prognostic factors of various functional outcomes such as AIS, Barthel Index, Spinal Cord Independence Measure, and respiratory dysfunction [ 20 , 21 , 22 ]. However, there has been a lack of research on developing prediction models that integrate such predictors.…”
Section: Discussionmentioning
confidence: 99%
“…The accurate prediction of prognosis for a certain disease or trauma has been one of the main goals of rehabilitation medicine. For this reason, many studies have been conducted to evaluate prognostic factors of various functional outcomes such as AIS, Barthel Index, Spinal Cord Independence Measure, and respiratory dysfunction [ 20 , 21 , 22 ]. However, there has been a lack of research on developing prediction models that integrate such predictors.…”
Section: Discussionmentioning
confidence: 99%
“…This study retrospectively analyzed multicenter registry data collected by the Japan Association of Spine Surgeons with Ambition (JASA) 20 22 . All study participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The JASA members, who are spine surgeons from 78 institutions in Japan, reviewed the medical records of their institutions and retrospectively registered the cases in the JASA database based on the following inclusion and exclusion criteria 20 22 . The following patients were included those aged ≥ 65 years with traumatic cervical SCI, those treated conservatively or surgically between 2010 and 2020 at one’s institution, and those followed up for at least 3 months post-injury.…”
Section: Methodsmentioning
confidence: 99%
“…There are several reports in the literature of arterial injury due to cervical spinal injury, which is a life-threatening condition (Table 1) 5,6) . A recent systematic review showed that the majority of the traumatic retropharyngeal hematoma with respiratory symptoms was in geriatric patients with falls or traffic accidents whose symptoms developed within 24 h of blunt trauma, and surgical treatment was performed in 23% of patients 7) .…”
Section: Insufficiency: a Case Reportmentioning
confidence: 99%